OASE SPIRITUAL PESANTREN DI NUSANTARA : STRATEGI MEMBANGUN EMOTIONAL SPIRITUAL QUOTIENT (ESQ) SANTRI - Islam, Syaiful (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2018)
This study presents the strategy of Building Emotional-Spiritual Quotient santri in pesantren Nurul Jadid, Paiton, Probolinggo, East Java. Emotional-spiritual intelligence, making students have intellectual, emotional and spiritual intelligence, is very necessary to be developed in pesantren. Emotional intelligence generates thoughts and actions. Whereas spiritual intelligence leads humans to understand the meaning of happiness through prosocial behavior. Happy as a subjective feeling, more about how someone has a sense to interpret. The sense in question is a sense of meaning for other human beings, for nature, and especially for the great power that humans realize is God. This study uses qualitative with case study approach. The results showed that, the strategy of the pesantren in developing the emotional- spiritual intelligence santri in Nurul Jadid Paiton Probolinggo was carried out through; first, equating the perceptions of the pesantren community about the importance of emotional-spiritual intelligence, habituating Islamic behavior to all components of the pesantren, strengthening the activities of santri in pesantren, making binding regulations for santri, muhasabah carried out periodically by the pesantren component.